Facilitating the development of self-concept skills in the classroom among trainee teachers. - Thabethe, Pauline Poppy Ntombi (My University, 1991)
There is generally a lack of research in the area of self concept development in the classroom, as related to Black education in general, and at Black colleges of education in particular. The importance of self-concept in the academic situation and the need to develop it in Black education was a motivating reason for the current research study. The study was undertaken at the Soweto College of Education. (Abbreviation abstract)
A RESEARCH REPORT SUBMITTED TO THE DIVISION OF SPECIALIZED EDUCATION, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG, IN PARTIAL FULFILMENT OF THE REQUIREMENTS OF THE DSGREE OF MASTER OF EDUCATION (SCHOOL COUNSELLING)
Keywords: Self-perception in children.; Motivation in education -- South Africa -- Soweto.; Teacher-student relationships -- South Africa -- Soweto.; Self-actualization (Psychology); Blacks -- Education -- South Africa -- Soweto.